Small D-type asteroids in the NEO population: new targets for space missions. Issue 4 (27th February 2018) - Barucci, Maria Antonietta; Perna, D; Popescu, M; Fornasier, S; Doressoundiram, A; Lantz, C; Merlin, F; Fulchignoni, M; Dotto, E; Kanuchova, S
Abstract : In the framework of the Near Earth Objects (NEOs) observational campaign carried out within the NEOShield-2 project, we identify nine new small D-type asteroids with estimated diameter less than 600 m. The link with meteorites for this class of asteroids is weak and the best fit obtained is with the Tagish Lake meteorite for seven of them. D-type asteroids are believed to contain the most pristine material of the Solar system and could have delivered the pre-biotic material to the Earth. Our results double the known sample of the D-types in the NEO population and triple the candidates of this class for a sample-return mission (at very low Δ V ). Our finding increases considerably the number of targets for sample-return mission. A sample-return mission to a D-type asteroid will provide a major progress in understanding the early history of the Solar system and to investigate the origin of life on the Earth.